PERFORMANCE OF A HEAT PIPE SOLAR COLLECTOR WITH EVACUATEDPOLYCARBONATE FRONT COVER - Abbass, Omed Akber; Abduljabbar, Ayaz (Journal of Applied Engineering Science, 2022)
In this research, the effect of vacuum on the thermal efficiency of a heat pipe solar collector is investigated. A comparative study of solar energy loss through different transparent covering materials, including different thicknesses of clear Polycarbonate (PC) and glass sheets, is performed to choose the best covering material. The results of solar energy loss tests show that for a 4mm, and 6mm thickness covering materials, transparent PC sheets have 11% and 22% less solar energy loss respectively than glass sheets. Three cases of flat heat pipe solar collector with different covering designs that are: no cover, non-vacuumed, and vacuumed double layer PC sheets are tested. Results show that the combination of a 4mm high transmittance PC cover with vacuumed spacing results in an overall collector thermal efficiency of about 70% in comparison with only 57% for non-vacuumed double layer PC cover.